PEMBELAJARAN MENULIS TEKS DESKRIPSI DI KELAS VII SMP NEGERI 4 SATAP SUHAID TAHUN PEMBELAJARAN 2020/2021 - Robi Robi; Laurensius Salem; Syambasril Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research is motivated by, text-based Indonesian language learning is carried out by applying the principle that language should be viewed as text, the use of language is a process of selecting linguistic forms to express meaning, language is functional, and language is a means of forming human thinking skills (Kemendikbud, 2013: 5). In connection with these principles, it is necessary to realize that each text has a different structure. Learning to write is one of the objects of language skills that is needed, especially in expressing ideas, thoughts, and messages through text. A common problem in this research is "How to learn to write descriptive texts in class VII SMP Negeri 4 Satap Suhaid in the 2020/2021 school year." The subproblem of this research is "How is the planning of learning to write descriptive text in class VII SMP Negeri 4 Satap Suhaid in the 2020/2021 school year, how is the implementation of learning to write descriptive text, and how is the assessment of learning to write descriptive text". The general objective in this research is to describe learning to write descriptive text. This type of research is implementation research. The research method is descriptive method. The form of research is qualitative. Data collection techniques are observation, interview and documentation. Data collection tools are observation sheets, record sheets, and documentation tools. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Based on the results of data analysis, the teacher has implemented learning according to the 2013 curriculum because the teacher has implemented three approaches according to the demands in the syllabus. The teacher has carried out the core activities well and is in accordance with the 2013 curriculum, and in accordance with the aspects that have been designed, namely the aspects of mastery of learning materials have been carried out very well. It is better if teachers in the field of Indonesian language studies at SMP Negeri 4 Satap Suhaid should pay more attention to the basic competencies and achievement indicators contained in the RPP, so that the implementation of learning is in accordance with basic competencies and indicators of achievement. Keywords: Description Text, Learning Implementation, Writing.